Oxfordshire introduction - Morris, John; Thorn, Frank; Thorn, Caroline (The University of Hull)
The introduction discusses the administrative history of the county; the Hundreds; the state of the manuscript for the county; places entered under the wrong county; the editorial history of earlier versions of the notes, and the current state of the revision. Some material in this introduction derives from the original printed edition published by Phillimore (1978) and edited by John Morris.